1999
DOI: 10.1111/j.1939-165x.1999.tb01053.x
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Study of Canine Pancytopenia

Abstract: To better define the incidence and causes of canine pancytopenia, we retrospectively evaluated the results of complete blood counts submitted to the University of Minnesota Veterinary Teaching Hospital during a 1-year period. Pancytopenia was defined as packed cell volume < 36%, total leukocyte count < 6,000/microliter or total segmented neutrophil count < 3,000/microliter, and platelet count < 200,000/microliter. Of 4,560 complete blood counts, 110 (2.4%) samples from 51 dogs met the criteria for pancytopenia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
1
20

Year Published

2001
2001
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(58 citation statements)
references
References 22 publications
2
35
1
20
Order By: Relevance
“…A study in the United States evaluated 4560 animals where 2.4% were pancyitopenics (WEISS et al, 1999). Another study in the same teaching hospital identified the non-endemic character for some diseases in the region, scoring as a possible factor that could explain their smaller found prevalence (WEISS, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A study in the United States evaluated 4560 animals where 2.4% were pancyitopenics (WEISS et al, 1999). Another study in the same teaching hospital identified the non-endemic character for some diseases in the region, scoring as a possible factor that could explain their smaller found prevalence (WEISS, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis is unclear, but by the response to immunosuppressive therapy presented, there is an evidence of immunemediated mechanism (WEISS, 2003;WEISS et al, 1999;BRAZZELL;WEISS, 2006). In the event of pancytopenia, it can be deduced a chronic aplasia, since the half-life of erythrocytes is long, the last citopenia to occur.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations